Process Damage Analysis and Cryoprotectant Optimization for Micro-droplet Spray Vitrification - Peng Tian; Zhang Xiaomin; Zhou Xinli (Zhileng xuebao)
Micro-droplet spray vitrification system produces small droplets and can be vitrified at a lower concentration of cryoprotectant (CPA). In this study, HepG2 cells were vitrified using micro-droplet vitrification system; moreover, damages caused by CPA loading, spraying, receiving, and vitrification/rewarming processes were evaluated. In addition, CPA formulations were optimized by reducing the Me2SO concentration and adding an appropriate amount of trehalose. The results showed that each step in micro-droplet spray vitrification may cause damage to the cells. CPA loading, spraying, vitrification and rewarming processes caused severe damages, but mild damages were caused by the sheet receiving process. Cell activities after cryopreservation are significantly reduced with a decrease in the Me2SO concentration. When the CPA formulations are constant, cell activities in the vitrification group become better than those in the slow freezing group. Moderate amounts of trehalose can enhance the effect of cryopreservation, while excessive trehalose can be counteractive. When cells were preserved with 5% Me2SO + 0.3M trehalose as a cryoprotectant, the cell survival rate reached (92.42±0.95)% and the 24 h adherence rate reached (95.64±1.03)%; therefore, the droplet spray vitrification effect was found to be the best.